Lawyers and legal culture in British North America : Beamish Murdoch of Halifax - Girard, Philip; Osgoode Society for Canadian Legal History (Toronto [Ont.] : Published for the Osgoode Society for Legal History by University of Toronto Press, 2011)
"From award-winning biographer Philip Girard, Lawyers and Legal Culture in British North America is the first history of the legal profession in Canada to emphasize its cross-provincial similarities and its deep roots in the colonial period. Girard details how nineteenth-century British North American lawyers created a distinctive Canadian template for the profession by combining the strong collective governance of the English tradition with the high degree of creativity and client responsiveness characteristic of U.S. lawyers - a mix that forms the basis of the legal profession in Canada today. Girard provides a unique window on the interconnections between lawyers' roles as community leaders and as legal professionals. Centred on one pre-Confederation lawyer whose career epitomizes the trends of his day, Beamish Murdoch (1800-1876), Lawyers and Legal Culture in British North America makes an important and compelling contribution to Canadian legal history."--Pub. desc.
Antecedents -- Apprenticeship -- The Legal Profession in Nova Scotia: Organization and Mobility -- The Making of a Colonial Lawyer, 1822-1827 -- The Maturing of a Colonial Lawyer, 1828-1850 -- The Politics of a Colonial Lawyer: Murdoch, Howe, and Responsible Government -- Law and Politics in the Colonial City: Murdoch as Recorder of Halifax, 1850-1860 -- Law, Identity and Improvement: Murdoch as Cultural Producer.
Includes bibliographical references and index.
JSTOR
Keywords: Murdoch, Beamish, -- 1800?-1876.; Murdoch, Beamish, -- 1800?-1876; Lawyers -- Nova Scotia -- Biography; Practice of law -- Nova Scotia -- History -- 19th century; Halifax (N.S.) -- Biography; Droit -- Pratique -- Nouvelle-Écosse -- Histoire -- 19e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Lawyers & Judges; LAW -- Legal History; Lawyers; Practice of law; Nova Scotia; Nova Scotia -- Halifax; 1800-1899; Biographies; History